Sunset song [videorecording (DVD)] - Davies, Terence, 1945-; Deyn, Agyness; Mullan, Peter; Guthrie, Kevin (Actor); Gibbon, Lewis Grassic, 1901-1935 (Magnolia Home Entertainment, 2016)
Follows the life of a Scottish farm girl, Chris, as she searches for her independence against the odds, in an epic rite of passage story set just before the First World War. The war and the struggles Chris endures test her resolve for love and her idyllic country farm life.